Menyingkap Fakta dan Peristiwa Dibalik Tanda Nabi Yunus - Seri Damarwanti (SANCTUM DOMINE: JURNAL TEOLOGI, 2018)
The books of Old Testament refered to fulfillment the coming of the Messiah in the New Testament. So did the Book of Jonah has written, also the fulfillment of the Messiah in the Gospel. Behind the disagreement in identifying the Book of Jonah as a historical book or parable, an undeniable fact is derived from the words of Jesus Christ, which resulted in the conclusion that "the sign of Jonah" is the only indication of his death and resurrection; equal time : three days and three nights; equality of conditions, both Jonah and Jesus, experienced death for three days and three nights, descended into the abyss and the world of the dead; and on the third day "resurrected" back from the dead, where Jonah was vomited from the belly of the fish and Jesus rose again from His death in the tomb; equality of mission : Jonah and Jesus, aim to preach the message of salvation to all humans.